Luminescent glasses in art - Oliveira, Rosa Maria de
In this study the application of luminescent glasses under UV light in artworks is explored. Several lanthanide oxides were used in the glass composition to obtain different colours. A brief comparison with the conventional glass artwork using neon is made. Future conservation was taken into account and the compatibility studies of mixtures of different glasses were studied.